Health, Inequality, and Economic Development - Deaton, Angus (Journal of Economic Literature, 2003)
I discuss mechanisms linking health and inequality and review evidence for effects of income inequality on aggregate and individual mortality, over time and over space. I conclude that there is no direct link. Correlations come from factors other than income inequality itself, some of which are linked to broader notions of inequality and inequity that are most likely important for health. Whether income redistribution can improve population health does not depend on the existence of a direct link between income inequality and health and remains an open question.